2005
DOI: 10.1016/j.quascirev.2004.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic foraminiferal Mg/Ca as a proxy for past oceanic temperatures: a methodological overview and data compilation for the Last Glacial Maximum

Abstract: As part of the Multi-proxy Approach for the Reconstruction of the Glacial Ocean (MARGO) incentive, published and unpublished temperature reconstructions for the Last Glacial Maximum (LGM) based on planktonic foraminiferal Mg/Ca ratios have been synthesised and made available in an online database. Development and applications of Mg/Ca thermometry are described in order to illustrate the current state of the method. Various attempts to calibrate foraminiferal Mg/Ca ratios with temperature, including culture, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(183 citation statements)
references
References 102 publications
(167 reference statements)
8
167
1
7
Order By: Relevance
“…The primary SST proxies are also sensitive to changes in seasonality [48,49]. SSTs derived from foraminifera Mg/Ca are known to reflect the calcification temperature of the species, which is best represented by the warm season conditions [50]. Environmental preferences of alkenone-producing algae may bias their proxy data estimates towards warmer temperatures, particularly in regions affected by both upwelling and open ocean conditions [51].…”
Section: (B) Seasonality Of Model Responsementioning
confidence: 99%
“…The primary SST proxies are also sensitive to changes in seasonality [48,49]. SSTs derived from foraminifera Mg/Ca are known to reflect the calcification temperature of the species, which is best represented by the warm season conditions [50]. Environmental preferences of alkenone-producing algae may bias their proxy data estimates towards warmer temperatures, particularly in regions affected by both upwelling and open ocean conditions [51].…”
Section: (B) Seasonality Of Model Responsementioning
confidence: 99%
“…The Mg/Ca ratio in foraminiferal calcite is widely used to reconstruct seawater temperatures (Barker et al, 2005;Jonkers et al, 2010b;Lea et al, 2000;Mashiotta et al, 1999). However, Mg/Catemperature relationships are species specific and remain (largely) empirical and many studies have shown a tight biological control on Mg incorporation in foraminiferal calcite (Anand et al, 2003;Bentov and Erez, 2006;de Nooijer et al, 2014;Jonkers et al, 2012;Jonkers et al, 2013a;Lea et al, 1999;Spero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing past seasonality during times of different boundary conditions is therefore important to our understanding of the climate system (Denton et al, 2005). Many palaeoclimate proxies, such as foraminiferal Mg/Ca ratios (Barker et al, 2005) and alkenones (Rossell-Melé et al, 2004), can be biassed to a particular season and therefore provide some seasonal information. However, very few extra-tropical records have the resolution to capture the full seasonal cycle and therefore unequivocally reveal the relationships between past seasonality and mean climate.…”
Section: Introductionmentioning
confidence: 99%